2021
DOI: 10.36927/2079-0325-v29-is1-2021-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on mental health (literature review)

Abstract: The coronavirus disease (COVID- 19) caused by the novel Coronavirus strain SARS-CoV-2 was firstly identified in December 2019 in China. Later on, in 3 months it got the status of a global pandemic. The coronavirus disease (COVID-19) posed a number of new challenges and questions for the population, medicine, and particularly for psychiatry. In many cases, it triggered a psychogenic beginning of mental, psychosomatic and somatic diseases. The initial pathogenesis of the mental diseases existing among the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This causes negative psychological reactions such as distress and maladaptation [ 51 , 52 , 58 , 59 ]. According to the results of a study conducted in China, which included 1,200 participants, 54% of them rated the impact of COVID-19 as moderate or severe, 29% reported moderate-to-severe anxiety, 17% reported moderate-to-severe depressive symptoms, and more than 75% were worried that their relatives might be infected [ 42 , 60 , 61 ]. Another survey involving 53,000 respondents showed that 35% of participants experienced psychological stress: 29% from mild to moderate, and 5% severe [ 62 , 63 ].…”
Section: Viewsmentioning
confidence: 99%
See 3 more Smart Citations
“…This causes negative psychological reactions such as distress and maladaptation [ 51 , 52 , 58 , 59 ]. According to the results of a study conducted in China, which included 1,200 participants, 54% of them rated the impact of COVID-19 as moderate or severe, 29% reported moderate-to-severe anxiety, 17% reported moderate-to-severe depressive symptoms, and more than 75% were worried that their relatives might be infected [ 42 , 60 , 61 ]. Another survey involving 53,000 respondents showed that 35% of participants experienced psychological stress: 29% from mild to moderate, and 5% severe [ 62 , 63 ].…”
Section: Viewsmentioning
confidence: 99%
“…The Director General of the World Health Organization (WHO) Tedros Adhanom Ghebreyesus officially confirmed the existence of the “infodemic” and called for fighting against it, since having covered the whole world it significantly complicated the fight against the real problem of overcoming the COVID-19 pandemic [ 42 , 84 ]. In fact, the COVID-19 pandemic is the first pandemic in the world history that unfolded in the presence of Facebook and other social networks, and was therefore accompanied by unprecedented panic, the consequences of which significantly worsened the consequences of COVID-19.…”
Section: Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inevitable changes due to the pandemic situation generate a challenge to create relevant modifications of psychological and psychotherapeutic support. The major challenge of these modifications is highly preserve stability of the treatment environment and continuation of necessary patient's assistance in such strenuous conditions as quarantine [9][10][11].…”
Section: Introductionmentioning
confidence: 99%